Marketing Mix Analysis in Bang Al Fried Chicken Sales - Yunengsih, Neng; Rizki, Muhammad Irfan (Journal of Sustainable Economic and Business, 2025)
Objectives: This study aims to analyze the marketing strategies implemented by Fried Chicken Bang Al, a street food producer of ready-to-eat fried chicken. Specifically, it examines the application of the marketing mix (product, price, place, and promotion) in influencing sales performance. Methodology: The research employs a qualitative descriptive approach, utilizing Philip Kotler's marketing mix theory. Data credibility is ensured through triangulation, and the analysis follows an interactive process involving data collection, data reduction, data presentation, and conclusion drawing. Findings: The study reveals that Fried Chicken Bang Al has not fully optimized its marketing mix strategy. Weaknesses are identified in advertising, promotion, and location. While the location is relatively strategic, it lacks dine-in facilities. However, pricing is a strong point, as the affordability of Fried Chicken Bang Al makes it competitive in the market. Conclusion: The marketing mix plays a positive role in maintaining sales stability. To enhance consumer interest and increase sales, Fried Chicken Bang Al should further develop its marketing strategy, particularly in terms of location and promotional activities.